COMMUNITY TRANSPORT : Policy, Planning, Practice - Gillingwater, David; Sutton, John, 1948- (Transportation studies, 1995)
This book explores the strategic significance of community transport, identifies and analyses the key issues which face community transport, and presents an analytical and evaluative account of the role, status and future of community transport